Safety and immunogenicity following a homologous booster dose of a SARS-CoV-2 recombinant spike protein vaccine (NVX-CoV2373): a secondary analysis of a randomised, placebo-controlled, phase 2 trial. Issue 11 (November 2022) - Mallory, Raburn M; Formica, Neil; Pfeiffer, Susan; Wilkinson, Bethanie; Marcheschi, Alex; Albert, Gary; McFall, Heather; Robinson, Michelle; Plested, Joyce S; Zhu, Mingzhu; Cloney-Clark, Shane; Zhou, Bin; et al.
Summary: Background: Emerging SARS-CoV-2 variants and evidence of waning vaccine efficacy present substantial obstacles towards controlling the COVID-19 pandemic. Booster doses of SARS-CoV-2 vaccines might address these concerns by amplifying and broadening the immune responses seen with initial vaccination regimens. We aimed to assess the immunogenicity and safety of a homologous booster dose of a SARS-CoV-2 recombinant spike protein vaccine (NVX-CoV2373). Methods: This secondary analysis of a phase 2, randomised study assessed a single booster dose of a SARS-CoV-2 recombinant spike protein vaccine with Matrix-M adjuvant (NVX-CoV2373) in healthy adults aged 18–84 years, recruited from 17 clinical centres in the USA and Australia. Eligible participants had a BMI of 17–35 kg/m 2 and, for women, were heterosexually inactive or using contraception. Participants who had a history of SARS-CoV or SARS-CoV-2, confirmed diagnosis of COVID-19, serious chronic medical conditions, or were pregnant or breastfeeding were excluded. Approximately 6 months following their primary two-dose vaccination series (administered day 0 and day 21), participants who received placebo for their primary vaccination series received a placebo booster (group A) and participants who received NVX-CoV2373 for their primary vaccination series (group B) were randomly assigned (1:1) again, via centralised interactive response technology system, to receive either placebo (group B1) or a single booster dose of NVX-CoV2373 (5 μg SARS-CoV-2 rS with 50 μg Matrix-M adjuvant; group B2) via intramuscular injection; randomisation was stratified by age and study site. Vaccinations were administered by designated site personnel who were masked to treatment assignment, and participants and other site staff were also masked. Administration personnel also assessed the outcome. The primary endpoints are safety (unsolicited adverse events) and reactogenicity (solicited local and systemic) events and immunogenicity (serum IgG antibody concentrations for the SARS-CoV-2 rS protein antigen) assessed 14 days after the primary vaccination series (day 35) and 28 days following booster (day 217). Safety was analysed in all participants in groups A, B1, and B2, according to the treatment received; immunogenicity was analysed in the per-protocol population (ie, participants in groups A, B1, and B2) who received all assigned doses and who did not test SARS-CoV-2-positive or received an authorised vaccine, analysed according to treatment assignment). This trial is registered with ClinicalTrials.gov, NCT04368988 . Findings: 1610 participants were screened from Aug 24, 2020, to Sept 25, 2020. 1282 participants were enrolled, of whom 173 were assigned again to placebo (group A), 106 were re-randomised to NVX-CoV2373–placebo (group B1), and 104 were re-randomised to NVX-CoV2373–NVX-CoV2373 (group B2); after accounting for exclusions and incorrect administration, 172 participants in group A, 102 in group B1, and 105 in group B2 were analysed for safety. Following the active booster, the proportion of participants with available data reporting local (80 [82%] of 97 participants had any adverse event; 13 [13%] had a grade ≥3 event) and systemic (75 [77%] of 98 participants had any adverse event; 15 [15%] had a grade ≥3 event) reactions was higher than after primary vaccination (175 [70%] of 250 participants had any local adverse event, 13 [5%] had a grade ≥3 event; 132 [53%] of 250 had any systemic adverse event, 14 [6%] had a grade ≥3 event). Local and systemic events were transient in nature (median duration 1·0–2·5 days). In the per-protocol immunogenicity population at day 217 (167 participants in group A, 101 participants in group B1, 101 participants in group B2), IgG geometric mean titres (GMT) had increased by 4·7-fold and MN50 GMT by 4·1-fold for the ancestral SARS-CoV-2 strain compared with the day 35 titres. Interpretation: Administration of a booster dose of NVX-CoV2373 resulted in an incremental increase in reactogenicity. For both the prototype strain and all variants evaluated, immune responses following the booster were similar to or higher than those associated with high levels of efficacy in phase 3 studies of the vaccine. These data support the use of NVX-CoV2373 in booster programmes. Funding: Novavax and the Coalition for Epidemic Preparedness Innovations.